The Adsorption of Pentachlorophenol from Aqueous Solutions onto Exchanged Al-MCM-41 Materials - Kheira Marouf-Khelifa; Amine Khelifa; Ahmed Belhakem; Reda Marouf; Fatiha Abdelmalek; Ahmed Addou (Adsorption Science & Technology)
The ability of a mesoporous molecular sieve to adsorb chlorinated phenols was studied experimentally. Thus, the adsorption isotherms of pentachlorophenol (PCP) from aqueous solutions were measured on (M)Al-MCM-41 (M = Na + , K + , Cu 2+ , Cr 3+ ) at intervals of 10 K between 303 K and 323 K. The experimental isotherms obtained were of the S-type in terms of the classification of Giles and co-workers. The best fit of the adsorption isotherm data was obtained using the Freundlich model. The adsorption affinity of PCP increased in the order (K)Al-MCM-41 < (Cr)Al-MCM-41 < (Na)Al-MCM-41 < (Cu)Al-MCM-41. At the same temperature, the adsorption of PCP on (Cu)Al-MCM-41 was more pronounced compared to its adsorption on alumina-pillared montmorillonite and mesoporous alumina aluminium phosphates. Analysis of the isosteric curves showed that (Cu)Al-MCM-41 and (Na)Al-MCM-41 presented a heterogeneous profile. In contrast, (K)Al-MCM-41 and (Cr)Al-MCM-41 did not exhibit energetic heterogeneity throughout the entire range of coverage.